Anemia after kidney transplantation - Abdallah, Emad; Waked, Emam; Nabil, Malak (African Journal of Nephrology, 2010)
<p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Background: Anemia is a major cardiovascular riskfactor in renal disease. It might be appropriate toextrapolate this association of anemia with cardiovasculardisease to renal transplant recipients who continue tohave a significant cardiovascular risk.The aim of our study was to elucidate the prevalence andrisk factors of anemia after kidney transplantation. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Methods: We studied 118 stable adult kidney transplantrecipients [age at transplant ranged between 22 and 58,42 12], 74 (62.7%) were males and 44 were females(37.3%) who received allograft between December 1998and October 2008 and had at least 1 year of posttransplantfollow up data at Sugar Medical Center,Theodor Bilharz Research Institute (TBRI), and HealthInsurance Organization Cairo. Hemoglobin (Hb) level at6 months, and 1 year after renal transplantation wasrecorded, the eGFR was calculated using the MDRDformula. Risk factors for anemia were evaluated usingunivariate and multivariate regression analysis. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Results: Anemia (Hb <12 g/dl in females and <13 g/dl inmales) was common (28.8% at 6 months, 31.4% at 1year). Significant anemia (Hb <11 g/dl in females and<12 g/dl in males) was also common (15.3% at 6 months,16.8% at 1 year). Severe anemia (Hb <10 g/dl in bothgenders) at 6 months post-transplant was less commonaffecting 4 out of 118 (3.4%) patients. At 1 year, 8 out of118 (6.8%) had severe anemia. Univariate andmultivariate analysis showed that a higher serumcreatinine level and lower eGFR were significant riskfactors at 6 months and 1 year post transplant. At 1 year,in addition to higher creatinine level and lower eGFR,female gender and immunosuppressive drugs(azathioprine and sirolimus) also were significant riskfactors. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Conclusions: Anemia is common during the first yearafter kidney transplantation. High serum creatinine, loweGFR, female gender and immunosuppressive drugs[azathioprine, sirolimus] are independent risk factors forpost-transplant anemia.